At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Akiko, Kato; Krafft, Bjørn A; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS One, 2016)
Kommersielle fiskerier kan påvirke marine økosystemer og bestander av topp-predatorer som sjøfugl. I Sørishavet foregår et ekstensivt fiske etter Antarktisk krill (Euphausia superba), og dette er antatt å øke. En sammenligning av fordeling og uttak hos fiskeriene og tilsvarende hos topp-predatorene er nødvendig for å forutsi fiskerirelaterte påvirkninger på krillavhengige predatorer. I dette studiet kartla vi næringssøksområdene hos Antarktispetrell (Thalassoica antarctica) som hekker i verdens største koloni (Svarthammaren, Dronning Maud land) over en treårsperiode. Vi fant at det romlige overlappet mellom krillfiskerier og næringssøkende Antarktispetrell generelt var lite. Konkurranse mellom Antarktispetrell og krill-fiskerier er for tiden neglisjerbart, men kan øke hvis fiskeriet etter krill øker.
Keywords: Dronning Maud Land; Sørishavet; fiskeriforvaltning; krill; marinbiologi; ornitologi; økosystem

Den norsk-brittisk-svenska Antarktisexpeditionen (NSBX) - Holmlund, Per; Martinsson, Tyrone (Frusna ögonblick : svensk polarfotografi 1861-1980, 2016)
Keywords: Antarktis; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fotografi; fotohistorie; polarekspedisjoner

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

Jason-ekspedisjonene 1892-1894, Antarctic-ekspedisjonen 1901-1904 - Larsen, Carl Anton; Kløver, Geir O (Red.) (Frammuseet, 2016)
Publication Title: Carl Anton Larsens dagbøker
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Sørishavet; dagbok; ekspedisjoner; hvalfangere; hvalfangst; polarområdene

Gåten om Roald Amundsens varde på Bettyfjellet i Antarktis - Mehlum, Fridtjof (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Polheim: teltet på Sydpolen - Melgård, Anne (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Publisher: Cambridge University Press
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

"Big Science" for meteorologene - Nilsen, Yngve; Vollset, Magnus (Vinden dreier : meteorologiens historie i Norge, 2016)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi

Ice core evidence for a 20th century increase in surface mass balance in coastal Dronning Maud Land, East Antarctica - Philippe, Morgane; Tison, Jean-Louis; Fjøsne, Karen; Hubbard, Bryn; Kjær, Helle A; Lenaerts, Jan T M; Drews, Reinhard; Sheldon, Simon G; De Bondt, Kevin; Claeys, Philippe; Pattyn, Frank (The Cryosphere, 2016)
Ice cores provide temporal records of surface mass balance (SMB). Coastal areas of Antarctica have relatively high and variable SMB, but are under-represented in records spanning more than 100 years. Here we present SMB reconstruction from a 120 m-long ice core drilled in 2012 on the Derwael Ice Rise, coastal Dronning Maud Land, East Antarctica. Water stable isotope (δ18O and δD) stratigraphy is supplemented by discontinuous major ion profiles and continuous electrical conductivity measurements. The base of the ice core is dated to AD 1759 ± 16, providing a climate proxy for the past ∼ 250 years. The core's annual layer thickness history is combined with its gravimetric density profile to reconstruct the site's SMB history, corrected for the influence of ice deformation. The mean SMB for the core's entire history is 0.47 ± 0.02 m water equivalent (w.e.) a−1. The time series of reconstructed annual SMB shows high variability, but a general increase beginning in the 20th century. This increase is particularly marked during the last 50 years (1962–2011), which yields mean SMB of 0.61 ± 0.01 m w.e. a−1. This trend is compared with other reported SMB data in Antarctica, generally showing a high spatial variability. Output of the fully coupled Community Earth System Model (CESM) suggests that, although atmospheric circulation is the main factor influencing SMB, variability in sea surface temperatures and sea ice cover in the precipitation source region also explain part of the variability in SMB. Local snow redistribution can also influence interannual variability but is unlikely to influence long-term trends significantly. This is the first record from a coastal ice core in East Antarctica to show an increase in SMB beginning in the early 20th century and particularly marked during the last 50 years.
Keywords: Dronning Maud Land; glasiologi; iskjerner

C.A. Larsen : explorer, whaler & family man - Riffenburgh, Beau (Red.); Kløver, Geir O (Red.) (The Fram Museum, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Weddellhavet; hvalfangere; hvalfangst; oppdagelsesreiser; polarforskning

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Publisher: Agenda Antártica. Antarctic and Southern Ocean Coalition (ASOC)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder